Decorum und Mammon im Widerstreit? Adeliges Wirtschaftshandeln zwischen Standesprofilen, Profitstreben und ökonomischer Notwendigkeit - Cremer, Annette Caroline; Jendorff, Alexander (Höfische Kultur interdisziplinär. Schriften und Materialien des Rudolstädter Arbeitskreises zur Residenzkultur, 2022)
Entrepreneurial activity by nobles was highly debated in the European Early Modern period. Generally, it was considered socially inappropriate. Nevertheless, profit-oriented activities of the nobility were an economic necessity and an everyday matter. The volume traces this ambivalence, using European examples between 1600 and 1900 from various ranks of the nobility and different fields of economic activity. It shows that the involvement of the nobility in European economic processes should not be underestimated. The book opens up an underrepresented field of research for a more in-depth examination.